2020
DOI: 10.14202/vetworld.2020.2326-2329
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of canine hepatitis in stray dogs in Nineveh Province, Iraq

Abstract: Aim: The current study was conducted to explore evidence of hepatitis B virus (HBV) infection in dogs in Nineveh Province, Iraq. Materials and Methods: Serum samples of 78 dogs were used to (i) estimate levels of the antibodies against HBV through enzyme-linked immunosorbent assay and (ii) measure the activity of liver function enzymes. Results: Seropositive dogs for HBV constituted 9% of total tested dogs. The differences in seropositivity among males compared to females and among different ages were not st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Given the possibility of inter-species transmission, the evidence that some viruses circulate among both dogs and cats [ 302 ], and the presence of antibodies specific to HBV in canine sera from several studies [ 303 306 ], it was hypothesized that HBV-like viruses might also be harbored by dogs. In 2019, Hepadnavirus DNA was detected in dogs for the first time using PCR targeting the preS/S1 genomic region and the core gene of HBV.…”
Section: Hepadnavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the possibility of inter-species transmission, the evidence that some viruses circulate among both dogs and cats [ 302 ], and the presence of antibodies specific to HBV in canine sera from several studies [ 303 306 ], it was hypothesized that HBV-like viruses might also be harbored by dogs. In 2019, Hepadnavirus DNA was detected in dogs for the first time using PCR targeting the preS/S1 genomic region and the core gene of HBV.…”
Section: Hepadnavirusmentioning
confidence: 99%
“…In 2019, Hepadnavirus DNA was detected in dogs for the first time using PCR targeting the preS/S1 genomic region and the core gene of HBV. Hepadnavirus DNA was identified in 10% of sampled dogs [ 306 ]. In 2022, another study reported that 6.3% of canine sera samples tested positive by qPCR, and the virus became known as Domestic Dog Hepadnavirus (DDH) [ 307 ].…”
Section: Hepadnavirusmentioning
confidence: 99%